2021
DOI: 10.1371/journal.pone.0248425
|View full text |Cite
|
Sign up to set email alerts
|

Tet1 is not required for myeloid leukemogenesis by MLL-ENL in novel mouse models

Abstract: The Ten Eleven Translocation 1 (TET1) gene encodes an epigenetic modifying molecule that is involved in demethylation of 5-methylcytosine. In hematological malignancies, loss-of-function mutations of TET2, which is one of the TET family genes including TET1, are frequently found, while the mutations of TET1 are not. However, clinical studies have revealed that TET1 is highly expressed in some cases of the hematological malignancies including acute myeloid leukemia. Indeed, studies by mouse models using convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Compound C57BL/6 (B6) mice conditionally expressing cytomegalovirus early enhancer / chicken β actin ( CAG ) promoter–driven MLL-ENL by inducible Cre-estrogen receptor α chain (CreER) fusion protein expressed from the Rosa26 locus (C/Tg mice) have been previously described. 9 , 26 All animal studies were approved by the Animal Care Committee of Mie University (no. 24-34-re5).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compound C57BL/6 (B6) mice conditionally expressing cytomegalovirus early enhancer / chicken β actin ( CAG ) promoter–driven MLL-ENL by inducible Cre-estrogen receptor α chain (CreER) fusion protein expressed from the Rosa26 locus (C/Tg mice) have been previously described. 9 , 26 All animal studies were approved by the Animal Care Committee of Mie University (no. 24-34-re5).…”
Section: Methodsmentioning
confidence: 99%
“…LT-HSCs (CD150 + /CD48 − KSL), ST-HSCs (CD150 − /CD48 − KSL), MPP2 (CD150 + /CD48 + KSL) cells, and MPP3/4 (CD150 − /CD48 + KSL) cells of C/Tg mice, and KSL and c-Kit high Sca-1 − Lin − (hereafter designated MP) cells of wild-type B6 mice were purified from the respective bone marrow (BM) cells using a fluorescence-activated cell sorting (FACS) Aria II (BD Biosciences, Franklin Lakes, NJ). 9 , 26 In brief, lineage-depleted cells were isolated from BM mononuclear cells labeled with Lineage Cell Detection Cocktail-Biotin using a MACS cell separation system (Miltenyi Biotec, Auburn, CA). For purification of LT-HSCs, ST-HSCs, MPP2 cells, and MPP3/4 cells derived from C/Tg mice, lineage-depleted cells were stained with peridinin chlorophyll protein (PerCP)-Cy5.5-conjugated streptavidin, and phycoerythrin (PE)–conjugated anti-c-Kit (2B8), PE-Cy7–conjugated anti-Sca-1 (D7), allophycocyanin (APC)–conjugated anti-CD150 (TC15-12FL12.2), and brilliant violet 421 (BV421)–conjugated anti-CD48 (HM48-1) monoclonal antibodies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tet1 is involved in MLL-AML development by promoting the expression of oncogenic target genes such as Hoxa9, Meis1, and Pbx3 [95]. However, a recent study demonstrated that Tet1 is not required for AML pathogenesis in an MLL-ENL mouse model [116]. Such a discrepancy might be explained by a difference in the MLL-fusion gene or the techniques used for fusion gene induction.…”
Section: The Expression and Functions Of Tets In Human Hematologic Ma...mentioning
confidence: 99%